Abba-- God's greatest gift to us - Amaan Ali Bangash; Ayaan Ali Bangash (New Delhi : Roli Books, 2002)
On the life of Indian sarod maestro Ustad Amjad Ali Khan, b. 1945.
Keywords: Biography Sarod Players India; Instrumental Music; Music; Arts